The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/14680874211048144
|View full text |Cite
|
Sign up to set email alerts
|

Study on the ignitability of a high-pressure direct-injected methane jet using a diesel pilot, a glow-plug, and a pre-chamber

Abstract: Natural gas is a promising alternative fuel for internal combustion engines, it allows for a reduction of engine-out emissions without impairing high engine efficiencies. Although this approach is already utilized from small to large engine classes, it is almost exclusively based on the combustion of a premixed, homogeneous charge. For ignition, small engines use standard spark-plugs or pre-chambers, while large and lean-operated engines use pre-chambers and pilot injections. Direct high-pressure gas injection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The work presented by Vera-Tudela et al 2 showed the feasibility of using a pre-chamber system to ignite a high-pressure methane jet. It remains to be seen if the superior performance of the pre-chamber setup as shown in those experiments can be replicated in real engines where only one or two of the main gas jets can be ignited with a single pre-chamber.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The work presented by Vera-Tudela et al 2 showed the feasibility of using a pre-chamber system to ignite a high-pressure methane jet. It remains to be seen if the superior performance of the pre-chamber setup as shown in those experiments can be replicated in real engines where only one or two of the main gas jets can be ignited with a single pre-chamber.…”
Section: Resultsmentioning
confidence: 99%
“…As in the preceding study, 2 the experiments were performed in the Flex-OeCoS optical engine test facility. 35 This test facility allows for a wide range of operation conditions, such as compression and combustion pressures up to 140 and 240 bar, respectively, working at end-of-compression temperatures between 700 K and 1000 K, tunable flow/turbulence by varying the motor speed between 300 and 1800 rpm, adjustable air charge composition and high variability pneumatic-driven valve trains.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To study the pre-ignition of lube oil, a series of measurements related to pre-ignition onset will be performed with no additional ignition sources. [17][18][19][20] In particular, the determination of the inflammation phase as well as the flame kernel growth is of interest. Moreover, implications on the subsequent combustion phase and flame propagation will be acquired.…”
Section: Introductionmentioning
confidence: 99%